Age and growth of hilsa shad, Tenualosa ilisha (Hamilton, 1822) of the river Tentulia in Bangladesh - Karim, Rajaul; Roy, Krishna Chandra; Roy, Purobi Rani; Ahmed, Zoarder Faruque (Journal of Fisheries, 2015)
This study was carried out on age and growth of hilsa shad, Tenualosa ilisha in river Tentulia in Bhola district using monthly samples from January to December 2009 by checking annual rings or growth checks on hard parts. Age and growth of T. ilisha got progressed by direct fit of length frequency data both to standard and to modified von Bertalanffy growth models with ELEFAN I procedure where the predicted maximum total length were (TL∞) 41.88 cm for male and 52.40 cm for female. Powell-Wetherall procedure gave an initial asymptotic total length (TL∞) for both male and female 40.42 cm, 50.61 cm respectively. The values of Z/K were 3.362 for male and 2.626 for female. The growth co-efficient (K) was obtained as 1.40 year-1 for male and 1.00 year-1 for female. The von Bertalanffy growth equations in terms of body weight (BW) for both male and female were BWt=799.26[1-exp-1.40(t+0.002)]3 and BWt=1717.82[1-exp-0.99(t+0.013)]3 respectively. The length-weight relationship for both sexes were BW=0.0101 TL 3.02 for male and BW=0.0086 TL 3.08 for female. The value of coefficient of determination (R2) was estimated for both male and female species were 0.969 and 0.968.